Culturally-informed for designing motorcycle fire rescue: Empirical study in developing country - Ghazali, Ihwan; Tanjung, Tia; Semiun, Nasri (American Institute of Physics, 2024)
Fire must be responded to quickly and effectively. Difficulties in reaching the fire location may arise due to high traffic. Motorcycle fire rescue can be an alternative to first aid in challenging areas. However, these areas, characterized by diverse cultural backgrounds, require careful consideration. Culture significantly impacts how such rescue systems are perceived, accepted, and utilized. This study delves into the efficiency and implementation of motorcycle fire rescue systems across different contexts, focusing on their alignment with regional cultural norms. Objectives include assessing operational challenges, identifying cultural implications, proposing culturally sensitive design recommendations, evaluating acceptance and effectiveness, and suggesting strategies and policy enhancements to strengthen emergency response capabilities. A preliminary trial was conducted to validate the survey instrument, followed by statistical analysis such as structural equation modeling, confirmatory factor analysis, and satisfaction level assessments. Findings highlight how cultural attitudes shape design preferences, the need for adaptable approaches to overcome operational hurdles, and the importance of adhering to culturally relevant design principles for system efficacy. Field tests also suggest potential improvements in emergency response effectiveness. Recognizing cultural considerations is essential in designing motorcycle fire rescue systems to enhance emergency response in developing nations. Furthermore, aligned with sustainable urban development goals, this research provides policymakers with valuable insights and practical approaches for engaging stakeholders. Equipping designers with information to address motorcycle fire incidents using environmentally friendly solutions underscores the importance of crafting emergency response plans sensitive to cultural differences across diverse landscapes.